Malnutrition - Imran, Muhammad; Imran, Ali (IntechOpen, 2020)
Malnutrition is a major threat faced by the developing nations and it has caused a severe health care and economic burden. This menace causes severe structural and functional abnormalities that hinders the growth of the individual and nation. This book provides complete insight of the problem, pathophysiology, impact and rectifying strategies. Moreover, this book encompasses the different sections that highlight the problem in a sequential manner. Hopefully, this book will prove to be an aid for the reader to enlighten their knowledge regarding malnutrition and its tackling strategies.